Congenital cutaneous lymphadenoma. (5th September 2017) - Fernandez‐Flores, Angel; Nicklaus‐Wollenteit, Ina; Sathishkumar, Dharshini; Diba, Vicky; Richard, Bruce; Carr, Richard; Moss, Celia; Nagy, Anita; Ogboli, Malobi; Colmenero, Isabel
Abstract : Cutaneous lymphadenoma is an uncommon benign neoplasm often considered to be an adamantinoid variant of trichoblastoma. Lesions present in both sexes, between 14 and 87 years of age, and are mainly located on the head and neck. Cases in children are rare and there is only 1 previous case of a congenital lymphadenoma. An 8‐year‐old Asian girl presented with a congenital lesion on her forehead comprising 4 pink papules, the largest 5 mm in diameter. Microscopy revealed a well‐circumscribed tumor within the dermis and subcutis comprising well‐demarcated epithelial lobules of basaloid and clear cells with subtle peripheral palisading, growing in a collagenous stroma but lacking retraction artefact. A relatively dense accompanying predominantly lymphocytic inflammatory cell infiltrate including both T‐cells (CD3+) and B‐cells (CD20+) permeated the nodules and spilled into the stroma. CD68+ histiocytes and CD1a+ Langerhans cells were moderately numerous. This is the second case of congenital lymphadenoma which—in spite of its rarity in childhood—widens the diagnostic possibilities of cutaneous lymphoepithelial tumors in children.